Perceived Role of Counselling on Adolescents’ Career Decision Making in Selected Schools in Ibadan North Local Government Area, Oyo State (2012)
Career choice is one of the major decisions made during the adolescent stage of development. Wrong decisions have led to various lifelong psychological problems, poor performance and lack of achievement. Many of these children would have found themselves in the career before understanding what it entails. This has brought into focus the importance of counselling in solving adolescent students’ career decision challenges. The general objective of this study was to examine the perceived role of counselling on students' career decision making in selected secondary schools in Ibadan North Local Government area of Oyo State. The descriptive survey was conducted among one hundred and forty (140) adolescents selected through systematic random sampling method from a total study population of 260 respondents. Self-administered questionnaire was the major instrument used to elicit information from the respondents. Permission was sought and obtained from relevant authorities before data collection. Collected data were analyzed using chi square test at p<0.05, The findings revealed that the students perceived career counselling as having important role to play in their career decision making. Though majority of the students had received counselling but only a few were counselled on career choice. The tested hypothesis revealed a significant association between availability of counselling Services and perceived role of counselling in students’ future career choice (x2=7.935, p= 0.019). Students perceived counselling as being very important in helping them in making career choice. This Service is not well implemented in some of the schools. There is need for adoption of counselling Services as an instrument for adolescent future choice career needs in all secondary school levels in the federation. This will help in fostering good harmony in the educational System and also make the students have good choice in terms of career or vocational needs